Mortality and life-years lost following subsequent physical comorbidity in people with pre-existing substance use disorders: a national registry-based retrospective cohort study of hospitalised individuals in Czechia - Formánek, Tomáš; Krupchanka, Dzmitry; Mladá, Karolína; Winkler, Petr; Jones, Peter B (The lancet. Psychiatry, 2022)
BACKGROUND: Substance use disorders constitute a major global public health problem, attributable largely to their subsequent comorbidity with other health conditions. This study aimed to investigate the risk of all-cause death and life-years lost following hospitalisation for 28 subsequent physical comorbid conditions in people with a previous hospitalisation for substance use disorder, compared with matched counterparts without substance use disorder. METHODS: We did a retrospective cohort study on data from Czech nationwide registers of all-cause hospitalisations and deaths during the period from Jan 1, 1994, to Dec 31, 2017. The cohorts consisted of individuals who had initially been hospitalised between 15 and 70 years of age (index hospitalisation) and who were subsequently hospitalised with one or more of 28 comorbid physical health conditions. We included individuals with an index hospitalisation for substance use disorders and up to three counterparts without substance use disorders with a subsequent hospitalisation for the same physical health condition, with matching on sex, age (±3 years), work status, and discharge year at first hospitalisation for the subsequent condition. Data on ethnicity were not available. Risk of death due to any cause following the first hospitalisation for each physical health condition until Dec 31, 2017, and life-years lost after disease onset at ages 30, 45, and 60 years, and before 81 years of age, were examined. FINDINGS: From a total 56 229 563 records of hospitalisations identified, we included 121 153 people with hospitalisation for substance use disorders and 6 742 134 people without hospitalisation for substance use disorders in the study. The 28 condition-specific cohorts comprised a median of 6444 individuals (IQR 2033-12 358), ranging from 444 for multiple sclerosis to 36 356 for diseases of the circulatory system. Across the cohorts, the proportion of males ranged from 31·4% for thyroid disorder to 100·0% for prostate disorders. The mean baseline age ranged from 30·0 years (SD 9·1) for chronic viral hepatitis in people with pre-existing substance use disorders to 62·2 years (9·7) for Parkinson's disease in people without pre-existing substance use disorders. After adjusting for potential confounders using stratified Cox proportional hazards models, individuals with a pre-existing substance use disorder had an increased risk of death due to any cause after the onset of 26 out of 28 physical health conditions, relative to their counterparts without substance use disorders, with adjusted hazard ratios ranging from 1·15 (1·09-1·21) for chronic liver disease to 3·86 (2·62-5·67) for thyroid disorder. For seven subsequent health conditions, the risk of death was more than doubled in the group with pre-existing substance use disorders. When compared with the general population via mortality tables, people with pre-existing substance use disorders had substantial losses in life-years after the onset of most of the subsequent physical health conditions regardless of age of onset, and, for the majority of comorbidities, lost considerably more life-years than their counterparts without substance use disorders. INTERPRETATION: A history of hospitalisation for substance use disorders appears to have a significant negative effect on prognosis following the development of various subsequent physical health conditions. These findings strongly suggest that clinical vigilance and high-quality integrated treatment for people with substance use disorders could be life-saving and should be given higher priority on the public health agenda. FUNDING: National Institute for Health and Care Research Applied Research Collaboration East of England at Cambridge and Peterborough National Health Service Foundation Trust.
Keywords: poruchy spojené s užíváním psychoaktivních látek; State Medicine; Registries; Adult; dospělí; retrospektivní studie; registrace; Substance-Related Disorders; Humans; Česká republika; mužské pohlaví; komorbidita; lidé; Male; Retrospective Studies; Comorbidity; státní lékařství; Czech Republic